GAYA BAHASA PADA LIRIK LAGU GRUP SONETA DALAM ALBUM EMANSIPASI WANITA - Astuti, Rr. Dwi (JURNAL PESONA, 2015)
AbstractLanguage style that used by the writer in his work is thought and feelings which create an aesthetic work. This study aims to describe language style of Sonetaâs song lyrics in Emansipasi Wanita album. This album is the XIII albums of Sonetaâs group. Method of this study is qualitative descriptive method. Based on analysis result, language style found in the song lyrics of Emansipasi Wanita album is a rhetorical language style and figurative language. Rhetorical language style includes alliteration, assonance, euphemism, periphrasis, hyperbole and oxymoron. Meanwhile, the figurative language includes simile, metaphor, personification and synecdoche. Key Words: Language style, Rhetorical, Figurative, Song Lyric.Â